2012
DOI: 10.1063/1.3694536
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic energy release in fragmentation processes following electron emission: A time-dependent approach

Abstract: A time-dependent approach for the kinetic energy release (KER) spectrum is developed for a fragmentation of a diatomic molecule after an electronic decay process, e.g. Auger process. It allows one to simulate the time-resolved spectra and provides more insight into the molecular dynamics than the time-independent approach. Detailed analysis of the time-resolved emitted electron and KER spectra sheds light on the interrelation between wave packet dynamics and spectra.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Although computing the KER spectrum via Eq. 4is an approximation, known as the mirror image principle, [45][46][47] we found that it holds well in the case of Ar dimer. Note that the mirror image principle is invalid in the case of total ICD electron and KER spectra, which are obtained by summing the spectra of all decaying states.…”
Section: Nuclear Dynamics Calculationsmentioning
confidence: 64%
“…Although computing the KER spectrum via Eq. 4is an approximation, known as the mirror image principle, [45][46][47] we found that it holds well in the case of Ar dimer. Note that the mirror image principle is invalid in the case of total ICD electron and KER spectra, which are obtained by summing the spectra of all decaying states.…”
Section: Nuclear Dynamics Calculationsmentioning
confidence: 64%
“…( 1) is the wave-packet propagation formulation of the electronic decay (see Refs. [58][59][60]). For this purpose, we first need to construct the potential energy curves (PECs) of all electronic states involved in the process and calculate the lifetime of the decaying state.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For the computation of the ICD and KER spectra, we use the time-dependent formalism of wave-packet dynamics for the case of electronic decay (see, e.g., Refs. [58][59][60]71]). Within this approach, the nuclear dynamics of the ICD process can be described by wave packets propagating on the PECs involved.…”
Section: B Interatomic Coulombic Decay Electron Spectrum and Kinetic ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, an inner-valence ionized system, which undergoes ICD, fragments additionally in a Coulomb explosion of the final doubly ionized electronic state | f >. In this case, the KER spectrum, that is, the distribution probability over the kinetic energy ε n of all dissociation fragments in the center-of-mass frame, is given by the projections of the final wave packet onto a set of the continuous vibrational wave functions | v f > via 173 , 174 …”
Section: Theoretical Approachesmentioning
confidence: 99%